(untitled) (Atti del Sodalizio Glottologico Milanese, 2021)
This article deals with the agreement system of two dialects spoken in southern Switzerland. In both, FPL agreement is marked by the suffix -n, which is a reflex of the 6th person verbal ending. In Bregagliotto, the more conservative dialect of the two, -n occurs in the second position of FPL NPS (FPL and FSG NPs are otherwise identical). In Mesolcinese, -n occurs on all inflected elements that agree with a feminine plural controller (including finite verbs), except definite articles and subject clitics.